The Histopathology of the Degenerative Proximal Biceps Tendon. Issue 7 (29th July 2019) - Dekker, Travis John; Chen, Angel; Kwon, Nicholas J.; Steele, John; Eward, William C.; Garrigues, Grant; Adams, Samuel Bruce; Toth, Alison P.
Objectives: Surgical treatment of proximal biceps tendinopathy remains a source of great controversy. Current surgical treatment debates center around the fixation location and not the quality of the tendon because little is known about the intra-tendinous pathology to guide this debate. Therefore, this study aims to evaluate two distinct anatomic regions of pathologic biceps tendons with regard to intra-tendinous architecture, painful neurotransmitters, and inflammatory modulators: the intra-articular portion and the extra-articular portion lying in the bicipital groove. Methods: Eleven human degenerative biceps tendons were obtained post-tenodesis. They were divided into intra- and extra-articular portions. They underwent histologic staining with hematoxylin and eosin and Alcian blue as well as immunohistochemistry staining for substance P, tyrosine hydroxylase, and neurofilament. Tendon architecture was assessed according to the modified BONAR tendon score. Immunohistochemistry staining was quantified using ImageJ density analysis. Portions of the tendon sections were cultured for 48 hours and the resultant secretome was assessed for Substance P secretion with ELISA analysis. Results: Composite BONAR scores demonstrated pathologic tendons with no significant difference between the intra-articular biceps tendon and the portion of the tendon within the bicipital groove (p= 0.31). Immunohistochemistry (IHC) analysis demonstrated significantly (p<0.05) increased uptake of substance P in the bicipital groove tendon compared to the intra-articular tendon while tyrosine hydroxylase did not (p>0.05). Stained substance P and tyr hydroxylase was intimately associated with intra-tendinous vascularity. ELISA results demonstrated significantly increased secretion of substance P in the bicipital groove tendon compared to the intraarticular portion. Conclusion: This study shows abnormal architecture, increased release and staining of painful neurotransmitters, and secretion of substance P from the proximal biceps tendon up to the distal aspect of the bicipital groove. Despite varied surgical techniques for tenodesis, this study supports the removal of the entirety of the long head of the biceps to the distal portion of the bicipital groove. Figure 2. Biceps tendon sample from within the bicipital groove of patient 12. Neg control stained slide depicted in A (Vessels containing red blood cells highlighted by red arrows). B highlights general increased density and uptake of Sub P (brown stain) as well as even greater density of substance P around the intratendinous vasculature. C shows similar findings with staining of Tyr Hydroxylase. Figure 3. Example BONAR tendon scoring for patient five. The panel on the far left is H&E staining at 100x used to determine vascularity. The middle panel is H&E at the same location at 200x to determine collagen structure and nuclei morphology. Lastly, the panel on the right are the same samples stained with Alcian blue and counterstained with eosin to evaluate the ground substance. The structures of both zones demonstrate hypervascularity, disorganized collagen matrix, rounded nuclei and abundant mucin staining with loss of bundle demarcation.